2014
DOI: 10.4047/jap.2014.6.6.491
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abutment materials on the implant-abutment joint stability in internal conical connection type implant systems

Abstract: PURPOSEThis study evaluated the influence of abutment materials on the stability of the implant-abutment joint in internal conical connection type implant systems.MATERIALS AND METHODSInternal conical connection type implants, cement-retained abutments, and tungsten carbide-coated abutment screws were used. The abutments were fabricated with commercially pure grade 3 titanium (group T3), commercially pure grade 4 titanium (group T4), or Ti-6Al-4V (group TA) (n=5, each). In order to assess the amount of settlem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…With an increase in this wear, there is a subsequent decrease in the detorque values, and during further prosthetic loading, the screw loses its threshold limit to engage into the grooves, and it either starts revolving around its own axis or tends to fracture. [7][8][9] Factors related to screw loosening are various, including poor tightening (inadequate preload), inaccurate fit of framework, poor component fit, flexure of framework, settling, debris trapped in screw receptor, screw design, and bone elasticity. 4,10,11, Various methods to combat this potential problem of screw loosening would include ensuring an adequate preload which supersedes the masticatory force, proper fit of the component, a considerably rigid framework, care taken to prevent entrapment of debris at the screw receptor site, choosing an appropriate screw design based on the nature of the bone, and coating of abutment screws.…”
Section: Discussionmentioning
confidence: 99%
“…With an increase in this wear, there is a subsequent decrease in the detorque values, and during further prosthetic loading, the screw loses its threshold limit to engage into the grooves, and it either starts revolving around its own axis or tends to fracture. [7][8][9] Factors related to screw loosening are various, including poor tightening (inadequate preload), inaccurate fit of framework, poor component fit, flexure of framework, settling, debris trapped in screw receptor, screw design, and bone elasticity. 4,10,11, Various methods to combat this potential problem of screw loosening would include ensuring an adequate preload which supersedes the masticatory force, proper fit of the component, a considerably rigid framework, care taken to prevent entrapment of debris at the screw receptor site, choosing an appropriate screw design based on the nature of the bone, and coating of abutment screws.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies support the superiority of the conical connection over the internal and the external hexagon, as the micro‐motions of the prosthetic abutment, the expanding of the micro‐gaps under pressure and the industrial stability are concerned . The conical connection (Figure ) is the type of internal connection that minimizes the gap between implant and prosthetic abutment with a Morse taper fit (conus in conus).…”
Section: Discussionmentioning
confidence: 99%
“…Abutment material could also influence the stability of the implant‐abutment connection. Jo et al compared the stability of the joint of three abutments made of commercially pure grade 3 titanium (group T3), commercially pure grade 4 titanium (group T4), or Ti‐6Al‐4V (group TA). It was found that preload and compressive bending strength values were significantly higher in group TA in contrast to groups T3 and T4.…”
Section: The Factors Contributed To Abutment Screw Looseningmentioning
confidence: 99%